Exploring The Role of ChatGPT in Chemistry Learning: A Systematic Literature Review - Priyadi*, Danang; Suyanta, Suyanta; Suwardi, Suwardi; Isa, Illyas Md (Universitas Syiah Kuala, 2025)
This study used the systematic literature review method to analyze the contribution of chatGPT in chemistry education by reviewing 30 related articles. The results showed that chatGPT assists in various learning tasks, such as preparing lesson plans, assessing students' critical thinking and self-regulation skills, guiding practical sessions, and supporting scientific report writing. In addition, chatGPT plays a role in the development of technology-based teaching materials and explaining complex chemical concepts. However, there are challenges in its implementation, such as the potential for students to rely on AI and the need for information verification to ensure the accuracy of scientific concepts. Therefore, in order for chatGPT to remain a useful tool in chemistry learning, it must be accompanied by the right strategy. With appropriate guidance, this technology can increase student interaction and engagement, thereby contributing to improving the quality of chemistry teaching in the digital era